Military justice : the rights and duties of soldiers and government - White, Nigel D. (United Kingdom: Edward Elgar Publishing, 2022)
'While military law is often narrowly understood and studied as the specific and specialist laws, processes and institutions governing service personnel, this accessible book takes a broader approach, examining military justice from a wider consideration of the rights and duties of government and soldiers engaged in military operations'--
Haslinda Isamail/ Fakulti Undang-Undang/ P118130@siswa.ukm.edu.my/ iquest/ CIP/ Innowawasan
Includes bibliographical references and index.
Keywords: Military law -- Great Britain; Soldiers -- Legal status, laws, etc. -- Great Britain; Civil-military relations -- Great Britain